Analysis of Phraseological Units Related to Profession in English Uzbek Languages - Akramxodjayeva Dilfuza Abduganiyevna (Journal of Higher Education and Academic Advancement, 2024)
In this article, the semantic analysis of phraeological units related to profession in the English and Uzbek languages shows that the proverbs and sayings of the studied languages cover all aspects of the life of different peoples in terms of their content. Phraseological units related to profession in English and Uzbek are semantically divided into nominative and communicative phraseological units. The verb of these phraseological units introduces phraseological units. Such units are less common in Uzbek than in English.